2015
DOI: 10.1007/s40980-015-0006-0
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and Spatial Patterns of Internal Migration in India

Abstract: With an urbanization level of 31.16 % in 2011, India is the least urbanized country among the top 10 economies of the world. In addition, unlike other countries, the transition of workforce out of agriculture is incomplete. This coupled with jobless growth in recent years has contributed to an increase in certain migration streams. While rural-rural migration continues to be the largest in terms of magnitude, we also document an increase in two-way commuting across rural and urban areas. Further, there are a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…Facing underemployment, flexible labor markets, uncultured labor skills, and a dearth of public services and social security, the opportunity costs and risks faced by transferring laborers are enormous when they completely abandon agricultural production, and transfer to uncertain off-farm job markets. Thus, short-term, round-trip, or seasonal transfer (part-time rural households) of rural labor have become their best choice (Figure 8) [1,26].…”
Section: Multi-pattern Of Rural Labor Transfermentioning
confidence: 99%
“…Facing underemployment, flexible labor markets, uncultured labor skills, and a dearth of public services and social security, the opportunity costs and risks faced by transferring laborers are enormous when they completely abandon agricultural production, and transfer to uncertain off-farm job markets. Thus, short-term, round-trip, or seasonal transfer (part-time rural households) of rural labor have become their best choice (Figure 8) [1,26].…”
Section: Multi-pattern Of Rural Labor Transfermentioning
confidence: 99%
“…There are almost 400 cities around the world that contain more than a million residents and about seventy % of these are in less developed countries. Chandrasekhar and Sharma (2015) suggested that there is a need to develop methods for estimating urban growth and migration simultaneously. D'Souza (1982) found that urbanization of scheduled caste in Punjab follows a set of patterns in the rural urban migration fewer people among the scheduled castes go to the cities than among the rest of the population and greater the occupational complexity of the city the lower is the representation of scheduled caste population.…”
Section: IImentioning
confidence: 99%
“…Natural population growth has played a much larger role in India's urbanization, thanks to its much higher fertility rate. 3 In contrast, migrant workers accounted for only 21 % of India's urban growth in recent decades but contributed nearly half of China's urban employment in 2007 (Chandrasekhar and Sharma 2015;Cai et al 2009). …”
Section: Comparison Of Labor Mobility In China and Indiamentioning
confidence: 99%